2021
DOI: 10.1093/noajnl/vdab020
|View full text |Cite
|
Sign up to set email alerts
|

Selumetinib normalizes Ras/MAPK signaling in clinically relevant neurofibromatosis type 1 minipig tissues in vivo

Abstract: BACKGROUND The MEK1/2 inhibitor selumetinib was recently approved for Neurofibromatosis type 1 (NF1)-associated plexiform neurofibromas, but outcomes could be improved and its pharmacodynamic evaluation in other relevant tissues is limited. The aim of this study was to assess selumetinib tissue pharmacokinetics and pharmacodynamics using a minipig model of NF1. METHODS Eight wild type (WT) and eight NF1  +/- (NF1) minipigs re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Single-dose PK of PD0325901 showed a similar PK profile to NF1 patients in clinical trials and exhibited a robust PD effect in PBMCs isolated from treated minipigs [29]. Selumetinib, the first FDA-approved therapy for NF1, was also evaluated in NF1 +/R1947X and WT littermates, and plasma PK and PD profiles of selumetinib aligned with those of NF1 patients [90,[110][111][112][113]. We also had the unique opportunity to evaluate the pharmacology of selumetinib in tissues clinically relevant to NF1, including cerebral cortex, optic nerve, sciatic nerve, and skin.…”
Section: Nf1 Genetically Engineered Swine Modelsmentioning
confidence: 76%
See 1 more Smart Citation
“…Single-dose PK of PD0325901 showed a similar PK profile to NF1 patients in clinical trials and exhibited a robust PD effect in PBMCs isolated from treated minipigs [29]. Selumetinib, the first FDA-approved therapy for NF1, was also evaluated in NF1 +/R1947X and WT littermates, and plasma PK and PD profiles of selumetinib aligned with those of NF1 patients [90,[110][111][112][113]. We also had the unique opportunity to evaluate the pharmacology of selumetinib in tissues clinically relevant to NF1, including cerebral cortex, optic nerve, sciatic nerve, and skin.…”
Section: Nf1 Genetically Engineered Swine Modelsmentioning
confidence: 76%
“…We also had the unique opportunity to evaluate the pharmacology of selumetinib in tissues clinically relevant to NF1, including cerebral cortex, optic nerve, sciatic nerve, and skin. Selumetinib was detectable in all tissues within two hours of oral administration, and significant inhibition of p-ERK was observed in skin and sciatic nerve from all minipigs [110]. Interestingly, basal p-ERK levels were significantly higher in NF1 +/R1947X minipig optic nerve compared to WT, which were efficiently reduced to WT levels with selumetinib [110].…”
Section: Nf1 Genetically Engineered Swine Modelsmentioning
confidence: 95%
“…NF1 (encoding the neurofibromin protein 1) is the major mutated gene in the germline of patients with neurofibromatosis type 1, which disrupts the regulation of the RAS / MAPK pathway [32] . Studies have shown that people with the disease with NF1 loss-of-function mutation, have a 5 times higher risk of breast cancer than the general population [33] .…”
Section: Discussionmentioning
confidence: 99%
“…NF1 provides a remarkable recent example. After a series of clinical trials, phase II registration trial of the MEK inhibitor selumetinib ( ClinicalTrials.gov, 2021 ; Herrick et al., 2021 ; Klesse et al., 2020 ; Osum et al., 2021 ), resulted in the FDA approval of a therapy for NF1 related inoperable plexiform neurofibromas in children. MEK is a kinase in the MAPK pathway, through which NF1 signals.…”
Section: Possible Therapeutic Targeting Strategies In Ndds and Cancermentioning
confidence: 99%